Model Driven RichUbi – Model Driven Process for Building Rich Interfaces of Context-Sensitive Ubiquitous Applications - Cirilo, Carlos Eduardo; Prado, Antonio Francisco do; Zaina, Luciana Aparecida Martinez (Anais do Concurso de Teses e Dissertações da SBC (CTD-SBC); 2012: Anais do XXV Concurso de Teses e Dissertações, 2012)
The demand for software in ubiquitous computing has raised new challenges for Software Engineering. One such challenge is related to the adaptation of applications accessed by different devices in multiple contexts of use. Amid this diversified scenario in access possibilities, Software Engineering is defied to innovate its processes and technologies so as to leverage development of solutions to effectively meet the adaptation requirements of ubiquitous environments. In response to these challenges, in this Master’s work we proposed a novel model driven process to address the content adaptation issues of rich interfaces for Web 2.0 applications which adapt themselves when viewed on distinct ubiquitous devices. With focus on software reuse, the process provides activities and artifacts that specially support the development of adaptive rich interfaces, contributing to save efforts and increase productivity. An experimental study demonstrated the potential of the proposed process to enhance efficiency, in terms of time and productivity, of teams developing adaptive rich interfaces.